A METHODOLOGICAL MODEL OF BUILDING NON-LINEAR LEARNING TRAJECTORIES DURING PRACTICAL LESSONS - Imomov Obidjon Elamonovich (American Journals, 2023)
In this article, the principles of development of professional competences of future engineers of higher educational institutions by developing project models of training based on a differential approach in practical training in physics are presented. During the practical lessons, the methodical model of building non-linear learning trajectories is explained and systematically described.
Keywords: paradigm, didactic principle, synergetic principle, methodology, concept, non-linear educational trajectories, differentiated education, innovative education.